Central bank digital currencies: An old tale with a new chapter - Michael D. Bordo; William Roberds (Federal Reserve Bank of Atlanta, 2022)
We consider the debut of a new monetary instrument, central bank digital currencies (CBDCs). Drawing on examples from monetary history, we argue that a successful monetary transformation must combine microeconomic efficiency with macroeconomic credibility. A paradoxical feature of these transformations is that success in the micro dimension can encourage macro failure. Overcoming this paradox may require politically uncomfortable compromises. We propose that such compromises will be necessary for the success of CBDCs.
Keywords: E42; E58; N10; 330; monetary systems; banknotes; central banks; digital currencies